2015
DOI: 10.1002/pc.23830
|View full text |Cite
|
Sign up to set email alerts
|

High performance PP/SEBS/CNF composites: Evaluation of mechanical, thermal degradation, and crystallization properties

Abstract: Nanocomposites comprising carbon nanofibers (CNF) were prepared and evaluated in terms of morphology, mechanical performance, thermal stability and crystallization properties. It was found that addition of CNF reinforced polypropylene (PP) matrix by marginally increasing the strength and modulus, but at the expense of toughness and ductility. To improve the toughness of the composites, polystyrene‐block‐poly(ethylene‐ran‐butylene)‐block‐polystyrene (SEBS) was used. Presence of SEBS remarkably improved the toug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…[ 17 ] Among other research studies, PP/SEBS blend is a good matrix in many domains, such as sports goods, automotive materials, and engineering materials for the excellent aging resistance. [ 18 ] Magnesium hydroxide (Mg(OH) 2 ) as a traditional flame‐retardant is widely used in polymers and engineering materials for the nontoxic and environmental‐friendly properties. [ 19,20 ] Recently, Liu et al [ 21 ] studied the surface modification Mg(OH) 2 on the flame‐retardant application of PP/SEBS matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Among other research studies, PP/SEBS blend is a good matrix in many domains, such as sports goods, automotive materials, and engineering materials for the excellent aging resistance. [ 18 ] Magnesium hydroxide (Mg(OH) 2 ) as a traditional flame‐retardant is widely used in polymers and engineering materials for the nontoxic and environmental‐friendly properties. [ 19,20 ] Recently, Liu et al [ 21 ] studied the surface modification Mg(OH) 2 on the flame‐retardant application of PP/SEBS matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Young's modulus increases with the addition of SiCO and shows a maximum value of 1906 ± 37.3 at 0.77 wt % SiCO composite. The increase in modulus is due to the following factors: (1) the presence of high modulus SiCO particles (2) reinforcement of SiCO particles with polymer matrix, and (3) increase in the crystallinity of the PLA composites by the addition of SiCO . However, at higher concentrations of the filler, the CO may act as a plasticizer and reduces the modulus of the composites.…”
Section: Resultsmentioning
confidence: 92%
“…The increase in modulus is due to the following factors: (1) the presence of high modulus SiCO particles (2) reinforcement of SiCO particles with polymer matrix, 40 and (3) increase in the crystallinity of the PLA composites by the addition of SiCO. 41 However, at higher concentrations of the filler, the CO may act as a plasticizer and reduces the modulus of the composites. The elongation at break of neat PLA (4.9%) gradually increases and a maximum of 8.8% is observed with the addition of 3.08 wt % SiCO.…”
Section: Characterization Of Sicomentioning
confidence: 99%
“…It was reported that mechanical properties were enhanced by the addition of CNFs [30]. In another study, CNF/PP/SEBS composites were fabricated; the toughness and ductility of the composites were reported to be improved [38]. In another study, Huang et al, fabricated CNF decorated flexible and super-hydrophobic polyurethane (PU)/SEBS composite nanofiber membranes.…”
Section: Stretchingmentioning
confidence: 99%